2022
DOI: 10.1007/s10072-022-06113-9
|View full text |Cite
|
Sign up to set email alerts
|

Lower serum triglyceride levels linked to more severe motor performance in Parkinson’s disease

Abstract: Introduction Emerging evidence has suggested that lipid metabolism is correlated with Parkinson’s disease (PD) onset and progression. However, the effect of lipid metabolism on motor performance in PD patients is still unknown. This study estimated the association between lipid profiles and the severity of motor performance in PD. Methods This cross-sectional study enrolled 279 idiopathic PD patients from the Department of Neurology of Beijing Tian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Besides, Li W et al and Jain M et al demonstrated that low serum TG levels worsened the prognosis in acute ischemic stroke [39,40] . Lower TG levels were also linked with higher hemorrhagic stroke risk in a prospective cohort study among 27,937 women [41] and more severe motor performance in Parkinson's disease [42] both of which are closely associated with diabetes [43][44][45] . Moreover, Statins, with the effect of decrease plasma TG concentration [46,47] and protective against NAFLD [48][49][50][51] and the development of liver fibrosis attributed to NAFLD [52] , has been reported to increased risk of new-onset diabetes by 12% (OR, 1.12) in an intensive-dose therapy compared with moderate-dose statin therapy [53] .…”
Section: Discussionmentioning
confidence: 96%
“…Besides, Li W et al and Jain M et al demonstrated that low serum TG levels worsened the prognosis in acute ischemic stroke [39,40] . Lower TG levels were also linked with higher hemorrhagic stroke risk in a prospective cohort study among 27,937 women [41] and more severe motor performance in Parkinson's disease [42] both of which are closely associated with diabetes [43][44][45] . Moreover, Statins, with the effect of decrease plasma TG concentration [46,47] and protective against NAFLD [48][49][50][51] and the development of liver fibrosis attributed to NAFLD [52] , has been reported to increased risk of new-onset diabetes by 12% (OR, 1.12) in an intensive-dose therapy compared with moderate-dose statin therapy [53] .…”
Section: Discussionmentioning
confidence: 96%
“…28 Unlike serum TG levels, serum Apo-A1, HDL-C, LDL-C and TC levels were not significantly associated with motor function, cognitive function or their deterioration in PD, which was consistent with previous research. 11,28 Thus, serum Apo-A1, HDL-C, LDL-C and TC levels do not seem to be significant indicators for assessing motor and cognitive function in PD.…”
Section: Discussionmentioning
confidence: 98%
“…10 Likewise, lower serum TG levels were associated with more severe motor performance in PD patients, indicating TG as a potential predictive biomarker for motor function. 11 Further research is needed to investigate the impact of blood lipid levels on motor and cognitive function over time. Therefore, this study aims to explore the relationship between blood lipid biomarkers and these indicators in individuals with PD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which TGs are involved in PD development and progression are unclear, but could be related to their role in neural communication, signal transduction, and cell membrane and mitochondrial functions [ 28 ]. Lower serum TG levels were associated with more severe motor performance effects in patients with PD [ 29 ]. Our findings indicate that lower TG levels might play a role in accelerating PD progression among early-stage PD individuals, and this could be a potential biomarker for monitoring the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%